Post-Surgical Outcome and Its Determining Factors in Patients Operated on With Focal Cortical Dysplasia Type II—A Retrospective Monocenter Study - Rácz, Attila; Becker, Albert J.; Quesada, Carlos M.; Borger, Valeri; Vatter, Hartmut; Surges, Rainer; Elger, Christian E. (Frontiers in Neurology, 2021)
Purpose: Focal cortical dysplasias (FCDs) are a frequent cause of drug-resistant focal epilepsies. These lesions are in many cases amenable to epilepsy surgery. We examined 12-month and long-term post-surgical outcomes and its predictors including positive family history of epilepsy. Methods: Twelve-month and long-term outcomes regarding seizure control after epilepsy surgery in patients operated on with FCD type II between 2002 and 2019 in the Epilepsy Center of Bonn were evaluated based on patient records and telephone interviews. Results: Overall, 102 patients fulfilled the inclusion criteria. Seventy-one percent of patients at 12 months of follow-up (FU) and 54% of patients at the last available FU (63 ± 5.00 months, median 46.5 months) achieved complete seizure freedom (Engel class IA), and 84 and 69% of patients, respectively, displayed Engel class I outcome. From the examined variables [histopathology: FCD IIA vs. IIB, lobar lesion location: frontal vs. non-frontal, family history for epilepsy, focal to bilateral tonic–clonic seizures (FTBTCS) in case history, completeness of resection, age at epilepsy onset, age at surgery, duration of epilepsy], outcomes at 12 months were determined by interactions of age at onset, duration of epilepsy, age at surgery, extent of resection, and lesion location. Long-term post-surgical outcome was primarily influenced by the extent of resection and history of FTBTCS. Positive family history for epilepsy had a marginal influence on long-term outcomes only. Conclusion: Resective epilepsy surgery in patients with FCD II yields very good outcomes both at 12-month and long-term follow-ups. Complete lesion resection and the absence of FTBTCS prior to surgery are associated with a better outcome.